2021
DOI: 10.1021/acs.molpharmaceut.1c00594
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Cyclic-Linear Cell-Penetrating Peptides Containing Alternative Positively Charged and Hydrophobic Residues as Molecular Transporters

Abstract: The cell membrane properties create a significant obstacle in intracellular delivery of cell-impermeable and negatively charged molecules. Herein, we report the synthesis and biological evaluation of a novel series of hybrid cyclic-linear peptides containing alternative positive and hydrophobic amino acids on the ring and side chain [(RW) 5 ]K(RW) X (X = 1−5) to compare their molecular transporter efficiency. The peptides were synthesized through Fmoc solid-phase peptide synthesis. In vitro cytotoxicity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Recently, cyclic linear hydrid peptides containing alternately Arg and Trp residues have been developed, as described in the text. Their transport efficiency of molecules for therapeutic purposes such as anti-HIV drugs with short incubation time has been demonstrated (Khayyatnejad Shoushtari et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, cyclic linear hydrid peptides containing alternately Arg and Trp residues have been developed, as described in the text. Their transport efficiency of molecules for therapeutic purposes such as anti-HIV drugs with short incubation time has been demonstrated (Khayyatnejad Shoushtari et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…They can transport small molecules that cannot penetrate through the cell membrane inside the cell. These peptides use energy-independent and energy-dependent pathways to penetrate the cell membrane . CPPs are used in different ways to mediate cellular cargo delivery, which are covalent conjugating with the cargo or creating stable noncovalent complexes. Some of these peptides can penetrate the cell without generating significant cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies showed that cyclic CPPs, [WR] 4 and [WR] 5 , with alternation of tryptophan (W) and arginine (R) residues, increased the cellular uptake of different compounds such as phosphopeptides, doxorubicin, ,,, paclitaxel, camptothecin, curcumin, , anti-HIV drugs, , gadolinium nanoparticles, selenium nanoparticles, gold nanoparticles, , and oligonucleotides. , Cyclic CPPs containing alternate W and R residues demonstrated improved cellular uptake delivery when compared to linear CPPs . Moreover, the uptake of both [WR] 4 and [WR] 5 was not dependent on the endocytosis pathway. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study demonstrated that uptake of the cargo was not only dependent on the CPP, it was conjugated too, but also on the cell line it was tested in, including HeLa, HEK, and HepG2 [ 30 ]. Khayyatnejad et al utilized a hybrid cyclic-linear CPP, ((RW) 5 )K(RW) X , to transport two different cargoes: a phosphopeptide and an anti-HIV drug [ 31 ]. While the goal of this study was to determine how the addition of positive and hydrophobic residues to the linear chain of the CPP affected uptake, it also demonstrated there was a significantly different uptake of these two different CPP/cargo complexes.…”
Section: Introductionmentioning
confidence: 99%